(untitled) (Gaceta Técnica, 2020)
The methodology for calculating the Prioritization Index for the Management of Seismic Risk in existing Buildings, came out as a result of the poor performance of structures that during the Cariaco 1997 earthquake, and the 1967 Caracas earthquake where the buildings collapsed, despite their apparent good state of conservation. In the case of four structures analyzed in this research, the Agustín Ocando Prosper School, the Agua Salobre Basic Bolivarian School, the Agustín Ocando Prosperous High School, and the Las Delicias Initial Education Center, these reinforced concrete buildings are located in the coastal zone of the Falcón State, in Venezuela, under the influence of the aggressive marine environment, and in the presence of the San Sebastian tectonic fault. The evaluation was carried out by applying the qualitative method of the Priority Index for Seismic Risk Management, verifying that the structures of the Agustín Ocando Prosperous School have a medium to high average vulnerability, however it is recommended to conduct detailed studies in modules 1 and 2 that have a very high frequency rating. For the Agua Salobre Bolivarian Basic School, the vulnerability index, corresponding to module 1, is medium high and the other group its classification is medium low; in Liceo Próspero Agustín Ocando modules 1 and 3 have a medium-high risk index and modules 1 and 3 are high. The Center of Initial Education Las Delicias, has the average risk index medium to low